Sustainability Business in Family Companies Through Good Corporate Governance Practices Related to Aspects of Business Legality in The Digital Era - Anis Tiana Pottag (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
The purpose of this study is to provide insight and education to family business actors to pay attention to the legality aspects of their business in the digital era by focusing on good corporate governance in order to create a sustainable business. This research uses the Quasi-Qualitative method to examine more deeply related to the improvement of Sustainability Business in Family Companies through Good Corporate Governance Practices and Aspects of Business Legality in the Digital Era. The object of research is the family company PT Tiana Pottag Group. Sample research using purposive sampling technique, namely family business owners (Owners), Directors of companies, and Representatives of the company's Legal Department. The data collection method uses in-depth interviews. The validity of data collection used the Triangulation technique. The analysis method uses the theory of Sustainability Business and the 5 main principles of GCG, namely fairness, transparency, accountability, responsibility, and stakeholders. As a result, Sustainability Business is an important factor because of the form of a company that can survive from time to time. Protection related to the legality of the business to get legal protection because of the frequent overlapping authority of the family company. The implementation of GCG principles in a family company helps the company to act professionally.